2015
DOI: 10.1007/s12160-015-9686-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Attenuates Physiological Stress Responses and Experimental Pain Sensitivity to Cold Pressor Pain

Abstract: Social support, not the mere presence of another individual, attenuated stress and pain during a CPT. Given the negative health consequences of stress and pain, clinical studies incorporating social support into medical procedures and treatments are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 92 publications
4
56
2
Order By: Relevance
“…A possible explanation could be that the relationship between practitioner and patient as established by the focus on the empathic relationship and emotional support in the SUPPORT group is equally important in patients' recovery. In fact, this relationship is also a well-known factor in placebo research (52,53) and other studies have shown that a supportive interaction style between practitioner and client (or social support in general) is associated with better outcomes (54,55). In our explorative look into moderation mechanisms, emotional impairment plays an important role which further underlines this interpretation.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…A possible explanation could be that the relationship between practitioner and patient as established by the focus on the empathic relationship and emotional support in the SUPPORT group is equally important in patients' recovery. In fact, this relationship is also a well-known factor in placebo research (52,53) and other studies have shown that a supportive interaction style between practitioner and client (or social support in general) is associated with better outcomes (54,55). In our explorative look into moderation mechanisms, emotional impairment plays an important role which further underlines this interpretation.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…50 Cross-cultural stresses and a lack of social support may interact to increase pain. These two factors could interact to increase pain and depression, as social support represents an important buffer against stress 35, 46 ; hence, the combination of acculturation stress and low social support may be particularly potent. In addition, the impact of acculturation stress and low social support may be magnified among Asian Americans with comorbid pain and depression; both are risk factors for pain and depression, 34, 37, 45, 59 which can, in turn, be mutually exacerbating.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, evidence for the relationship between social support and pain-related disability is often inconsistent (see review by Campbell et al, 2011). Some studies have shown that high social support in chronic pain patients is associated with lower levels of painrelated disability and avoidance of daily activities (e.g., Cohen & Wills, 1985;Evers et al, 2003;Hughes et al, 2014;Jamison & Virts, 1990;Roberts, et al, 2015;Turk et al, 1992). Meanwhile, other studies have demonstrated a positive association between social support and pain-related disability, increased pain behavior and dependence (e.g., Boothy et al, 2004;Kerns et al, 1991;Raichle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%